The Unaccompanied: Poetic Expressions of the Working Classes in England - Matthias Fechner (Anglica. An International Journal of English Studies)
Since the lost labour struggles of the mid-1980s, (working-class) poets like Carol Ann Duffy and Simon Armitage have progressively asserted their themes across the social strata. Hence, four of their poems are put to closer scrutiny. Especially Armitage’s verse mirrors a tendency in contemporary working-class poetry – frequently located in the North and the Midlands – to reflect on endangered traditions, with no small amount of nostalgia. Yet, its issues – solidarity, equality and historical consciousness – have also been taken up by black and female lyricists. Consequently, the poetry of the new working classes includes the concerns of all disadvantaged people of England (and the world).